The Epistemological Construction of The Qur'anic Hadith Law of Attraction Within The Framework of Contemporary Islamic Education - Muyassaroh, Iffah Khoiriyatul; Marhumah (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2026)
The Qur’anic-Hadith Law of Attraction (QHLoA) has gained visibility among urban Indonesian Muslims through seminars, training programs, and digital da’wah that combine Qur’anic verses, hadith, motivational discourse, inner healing, and everyday meaning-making. Existing studies have discussed this phenomenon as personal spirituality, religious motivation, or popular da’wah, while its epistemological implications for Islamic education remain underexplored. Using a qualitative, phenomenologically informed design, this study examines QHLoA practices in Yogyakarta and Semarang through interviews with participants, an alumnus, an organizer, facilitators, and local religious figures, supported by observations of seminars and training sessions and analysis of training and digital da’wah materials. The findings show that QHLoA constructs religious knowledge through the interaction of revelatory texts, inner experience, digital mediation, and practical life orientation. Inner experience functions as both a medium of spiritual internalization and a source through which participants validate the relevance of religious teachings. The study also identifies a tension between QHLoA’s affective-pragmatic appeal and the need for stronger tawhidic orientation, adab formation, and critical reflection. This article contributes to Islamic educational epistemology by showing how revelation, experience, and practical reasoning are negotiated in contemporary Muslim learning spaces. It also argues for reflective pedagogy grounded in theological depth and ethical responsibility